Size of recurrent symptomatic common bile duct stones and factors related to recurrence - Chang, Jae Hyuck; Kim, Tae Ho; Kim, Chang Whan; Lee, In Seok; Han, Sok Won (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Some common bile duct (CBD) stones recur after endoscopic stone extraction. Little information is available on the size and recurrence interval of recurrent symptomatic CBD stones or on ways to prevent recurrence. Materials and Methods: Between January 2007 and December 2011, consecutive 481 patients undergoing endoscopic extraction of CBD stones at a single institute were enrolled. We selected 34 patients with recurrent symptomatic CBD stones and 63 patients who were followed up more than five years without recurrence. Results: The sizes of the CBD stones increased during the recurrences: 10.1±5.2 mm, 13.5±7.3 mm, and 16.8±7.8 mm at the initial presentation, the first recurrence, and the second recurrence, respectively (p=0.016). Among CBD stone recurrences, 50% occurred within 2.3 years, and 80% occurred within 5.3 years. The recurrence group had a smaller proportion of patients under 50 years of age, larger CBD diameters, less histories of more than 10 mm endoscopic papillary large-balloon dilation (EPLBD), and more type I periampullary diverticula, compared with the non-recurrence group (p<0.05). Multivariate analysis revealed that EPLBD more than 10 mm and smaller CBD diameter were independently related to less recurrence of CBD stones (p=0.001 and 0.012, respectively). Conclusion: The sizes of CBD stones increased during recurrences. EPLBD more than 10 mm and smaller CBD diameter were related to less recurrence of CBD stones.